Disaggregating household food insecurity access scale indicators based on climate change impacts among smallholder farmers in KwaZulu-Natal Province, South Africa - Oladele, Oladimeji I.; Patekile, Nomcebo (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2026)
The growing threat of climate change has worsened food insecurity worldwide, particularly for smallholder farmers in KwaZulu-Natal (KZN) Province, South Africa. This study aims to compare the Household Food Insecurity Access Scale (HFIAS) indicators before and after the impacts of climate change on smallholder farmers in KZN in 2024. A systematic sampling approach, combined with a descriptive study design, was employed to select sixty farmers. Data on personal characteristics and HFIAS were collected, subjected to face validity and reliability tests, and analyzed using the Statistical Package for Social Sciences (SPSS) version 29, with frequency counts, percentages, and paired sample t-tests. The comparison of food security before and after the effects of climate change shows a significant difference (t = -6.70, p < 0.01). The findings suggest that climate change exacerbates food insecurity, particularly affecting elements such as food availability, access, perception, and insecurity prevalence. The study concludes that climate change has worsened food insecurity on smallholder farms, particularly by increasing dependence on purchased food. The policy implications emphasize areas that need targeted interventions, driven by increased indicators of food availability, access, perception, and insecurity following the onset of climate change. The study recommends strategies to enhance farmers' resilience, including expanding access to climate-smart agricultural technologies and extending agricultural extension services.